Phosphorus in Agriculture: 100 % Zero 2016
DOI: 10.1007/978-94-017-7612-7_5
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Plant Available P in Soil

Abstract: Fertilization should be based on a proper diagnosis of the plant nutritional status. Without, there is always the risk of under fertilization causing economic losses by not exploiting the yield potential of the site and its crop. On the opposite, over fertilization not only hampers fertilizer economy through inefficient nutrient rates, but also causes serious environmental impacts on neighboring ecosystems. There are four basic diagnostic methods each of which has its advantages and disadvantages: ceteris pari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 79 publications
(103 reference statements)
0
12
0
Order By: Relevance
“…Hence, several simple chemical extraction methods are used to estimate the plant-available P of soils [1,2]. More recently, several research groups [3][4][5][6][7][8] have shown that the Diffusive Gradients in Thin films (DGT) technique have a much better correlation to plant-available P in soils than standard chemical extraction tests (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, several simple chemical extraction methods are used to estimate the plant-available P of soils [1,2]. More recently, several research groups [3][4][5][6][7][8] have shown that the Diffusive Gradients in Thin films (DGT) technique have a much better correlation to plant-available P in soils than standard chemical extraction tests (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Although, compared with other widely used P extraction methods (e.g., Olsen, Mehlich, or Bray), CAL and DL are quite similar, there are differences that influence the comparability of both methods (Yli-Halla et al, 2016). Because of the higher pH value, CAL extracts a smaller portion of Ca-P, but a higher portion of Al-and Fe-P (Reichert, 1989;Yli-Halla et al, 2016).…”
Section: Equationmentioning
confidence: 99%
“…Phosphorus in soils can be separated into various fractions with different chemical properties (e.g., solubility, mobility) and different availability to plants (Cross and Schlesinger, 1995;Frossard et al, 2000). Only a relatively small fraction of total soil P is readily available for plant uptake (Frossard et al, 2000;Neyroud and Lischer, 2003;Yli-Halla et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The DGT technique has increasingly been acknowledged as superior for assessing soil P status in comparison with traditional extraction methods (Yli-Halla et al, 2016), and the method has also been suggested to be a useful method for predicting the growth response of plants to added P fertilizers (Six et al, 2013). Comparison of the ability of the DGT method and the more simple WEP method for their ability to predict plant P availability is therefore of interest.…”
Section: Effects Of Sludge Drying Temperature and Drying Processmentioning
confidence: 99%